2019
DOI: 10.1109/mits.2019.2919615
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Predicting Travel Time with Spatio-Temporal Features of Network Traffic Flow, Weather and Incidents

Abstract: Travel time on a route varies substantially by time of day and from day to day. It is critical to understand to what extent this variation is correlated with various factors, such as weather, incidents, events or travel demand level in the context of dynamic networks. This helps a better decision making for infrastructure planning and realtime traffic operation. We propose a data-driven approach to understand and predict highway travel time using spatio-temporal features of those factors, all of which are acqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 36 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…Matrix factorization can be viewed as an approach to reduce the dimensionality or compress Asif et al (2013) traffic data. Traffic data dimensionality techniques span more classical techniques building on principal component analysis Li et al (2007), Yang and Qian (2019), Li et al (2015), to more recent developments using variational autoencoders Boquet et al (2020). Exploiting spatio-temporal patterns can both support data reduction and also prediction of future traffic states on the network, Yang and Qian (2019).…”
Section: Related Workmentioning
confidence: 99%
“…Matrix factorization can be viewed as an approach to reduce the dimensionality or compress Asif et al (2013) traffic data. Traffic data dimensionality techniques span more classical techniques building on principal component analysis Li et al (2007), Yang and Qian (2019), Li et al (2015), to more recent developments using variational autoencoders Boquet et al (2020). Exploiting spatio-temporal patterns can both support data reduction and also prediction of future traffic states on the network, Yang and Qian (2019).…”
Section: Related Workmentioning
confidence: 99%
“…In these cases, past traffic dynamics on the target road segments may have little useful information implying their future traffic states. A widely used solution found in literature is to take into account spatiotemporal correlations between target road segments and nearby segments ( 19, 20 , 42 ). As it takes time for traffic to propagate, abnormal traffic nearby can work as longer-term predictors.…”
Section: Methodsmentioning
confidence: 99%
“…Linear regression models with L 1 regularization, that is, LASSO, which use the same feature set as the neural network model, are built for each segment i and prediction horizon h independently ( 19, 43 ). The model learns the weights w h ( i ) such that the loss in Equation 8 is minimized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in [ 46 ], RF can handle overfitting with sufficient speed when large data series are used, compared to other similar regression tree algorithms. A more recent study in [ 47 ] reported that RF achieved the lowest average errors compared to other regression models for predicting travel times across an urban road network. An empirical analysis in [ 48 ] acknowledged the limitation that fine-tuning is a time-consuming procedure.…”
Section: Related Workmentioning
confidence: 99%